2012
DOI: 10.1007/s00464-012-2291-7
|View full text |Cite
|
Sign up to set email alerts
|

Stent treatment of malignant gastric outlet obstruction: the effect on rate of gastric emptying, symptoms, and survival

Abstract: The present study demonstrated that treatment with SEMS results in improved gastric emptying in most patients with GOO and a corresponding reduction in self-reported obstruction symptoms. However, survival and emptying were not related. The present findings provide further evidence that treatment with stents is an effective palliative treatment in patients with GOO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…The effect of stent placement on the gastric emptying test could not be evaluated because the test was not also performed before stent placement 11 12 . Using analysis of 13C-octanoic acid breath test (OBT) results at 4 hours after a solid meal, Larssen et al reported that 82.4 % (14/17) of patients had DGE before stent placement whereas 52.9 % (9/17) had DGE after stent placement 12 . The observation that the gastric emptying function was impaired even after stent placement suggests that patients with malignant gastric outlet obstruction may have dysmotility of the stomach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of stent placement on the gastric emptying test could not be evaluated because the test was not also performed before stent placement 11 12 . Using analysis of 13C-octanoic acid breath test (OBT) results at 4 hours after a solid meal, Larssen et al reported that 82.4 % (14/17) of patients had DGE before stent placement whereas 52.9 % (9/17) had DGE after stent placement 12 . The observation that the gastric emptying function was impaired even after stent placement suggests that patients with malignant gastric outlet obstruction may have dysmotility of the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the stent effect can be provided by measuring the rate of gastric emptying before and after stent placement 11 12 . Larssen et al reported that treatment with stents resulted in improved gastric emptying in 76 % (13 /17) of patients with malignant gastric outlet obstruction, whereas gastric emptying was unchanged or worse in four patients (24 %).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 This procedure generally requires the patient to be fit enough for conscious sedation. A suitable endoscopic skill set is also required.…”
Section: Endoscopic Managementmentioning
confidence: 99%
“…7 Of these options the placement of a SEMS is currently the most frequently undertaken. 6 SEMS insertion is most likely to be carried out endoscopically with fluoroscopic assistance.…”
Section: Endoscopic Managementmentioning
confidence: 99%